Intrapleural infusion of tumor cell-derived microparticles packaging methotrexate or saline combined with pemetrexed-cisplatin chemotherapy for the treatment of malignant pleural effusion in advanced non-squamous non-small cell lung cancer: A double-blind, randomized, placebo-controlled study - Dong, Xiaorong; Huang, Yu; Yi, Tienan; Hu, Chunhong; Gao, Quanli; Chen, Yuan; Zhang, Jing; Chen, Jianhua; Liu, Li; Meng, Rui; Zhang, Sheng; Dai, Xiaofang; et al. (Frontiers in Immunology, 2022)
Background: Preclincal studies showed the promising efficacy of tumor cell-derived microparticles packaging methotrexate (TMPs-MTX) to treat advanced non-squamous non-small cell lung cancer (NSCLC) with malignant pleural effusion (MPE). Methods: This randomized, double-blind, placebo-controlled study was conducted at six hospitals in China from 20 July 2015 to 25 April 2019. Patients newly diagnosed with non-squamous NSCLC with MPE were randomly assigned to receive TMPs-MTX (group A) or saline (group B). Patients in both groups received pemetrexed (500 mg/m2 d1) and cisplatin (75 mg/m2 in total for d1-d2). Intrapleural infusion (50 mL saline containing 5 units of TMPs-MTX per perfusion, once every 48 hours, six total perfusions) was initiated on day 5 after pemetrexed-cisplatin chemotherapy. The primary outcome was the objective response rate (ORR) of MPE. Secondary outcomes included the ORR of target lesions, progression-free survival (PFS), overall survival (OS), toxicity, and pleural fluid properties. Results: A total of 86 patients were enrolled in this study and randomly assigned to either group A or group B. Of these, 79 patients were evaluable for response. The ORR of MPE in group A was significantly higher than that in group B (82.50% vs. 58.97%, P = 0.0237). The ORR of target lesions was 25.64% in group A and 20.51% in group B (P = 0.5909), respectively. With a median follow-up time of 18.8 months, median PFS were 6.4 (95% CI, 4.5-12.3) months in group A and 7.3 (95% CI, 6.1-10.4) months in group B (P = 0.6893), and median OS were 19.9 (95% CI, 17.1-28.5) months and 17.5 (95% CI, 11.6-25.0) months (P = 0.4500), respectively. The incidence rates of adverse events were similar in the two groups. The most common treatment-related adverse events were chemotherapy-induced toxicities, including fever, gastrointestinal reactions, hepatic dysfunction, and leukopenia. Conclusion: Intrapleural infusion of TMPs-MTX combined with pemetrexed-cisplatin chemotherapy is safe and effective against MPE in patients with advanced non-squamous NSCLC. Trial registration: This trial was prospectively registered on Chinese Clinical Trial Registry (ChiCTR-ICR-15006304).